The Routledge research companion to travel writing - Pettinger, Alasdair, 1959-; Youngs, Tim, 1961- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Showcasing established and new patterns of research, The Routledge Research Companion to Travel Writing takes an interdisciplinary approach to scholarship and to travel texts themselves. The volume adopts a thematic approach, with each contributor considering a specific aspect of travel writing - a recurrent motif, an organising principle or a literary form. All of the essays include a discussion of representative travel texts, to ensure that the volume as a whole represents a broad historical and geographical range of travel writing. Together, the 25 essays and the editors' introduction offer a comprehensive and authoritative reflection of the state of travel writing criticism and lay the ground for future developments.
Framing travel. The scientific traveller / Angela Byrne -- Nature writing / Paul Smethurst -- Migrant narratives / Aedín Ní Loingsigh -- The expatriate life / Lynn Mastellotto -- Travelling in pairs / Kathryn N. Jones -- Footsteps / Maria Lindgren Leavenworth -- Vertical travel / Charles Forsdick -- Modes of writing. Letters / Eve Tavor Bannet -- Diaries and journals / Christina Laffin -- Guidance and advice / Alasdair Pettinger -- Narrative / John Culbert -- Description / Benjamin Colbert -- Lectures / Tom F. Wright -- Sensuous geographies. Seeing / Margaret Topping -- Hearing / Tim Youngs -- Touching / Sarah Jackson -- Tasting / Heidi Oberholtzer Lee -- Smelling / Clare Brant -- Interactions -- Hospitality / Kevin J. James -- Foreign exchange / David Murray -- Between languages / Michael Cronin -- Animals / Elizabeth Leane -- Paratexts. Editorial matters / Michael G. Brennan -- Maps / James R. Akerman -- Book and print technology / Innes Keighren.
Includes bibliographical references and index.
Alasdair Pettinger is an independent scholar based in Glasgow, Scotland. He has published on travel literature, the cultures of slavery and abolitionism, and representations of Haiti. His books include the anthology Always Elsewhere (1998) and Frederick Douglass and Scotland, 1846 (2018). Tim Youngs is Professor of English and Travel Studies at Nottingham Trent University. His books include The Cambridge Companion to Travel Writing (edited with Peter Hulme, 2002), The Cambridge Introduction to Travel Writing (2013) and The Cambridge History of Travel Writing (edited with Nandini Das, 2019).
Online resource; title from digital title page (viewed on September 03, 2019).
eBooks on EBSCOhost
Keywords: Travelers' writings -- History and criticism; Travel writing -- History; Écrits de voyageurs -- Histoire et critique; Voyage -- Art d'écrire -- Histoire; LITERARY CRITICISM -- General; Travel writing; Travelers' writings; Electronic books; Criticism, interpretation, etc; History